2014
DOI: 10.1155/2014/619028
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Well‐Being and Quality of Life of Iranian Adults with Type 2 Diabetes

Abstract: Introduction. Diabetes is a major public health problem. Little is known about the spiritual well-being and its relationship with quality of life (QOL) in Iranian Muslim patients with diabetes. This study investigated the spiritual well-being and QOL of Iranian adults with type 2 diabetes and the association between spiritual well-being, QOL, and depression. Methods. A cross-sectional study was done among 203 patients with type 2 diabetes mellitus in Isfahan, Iran. Quality of life and spiritual well-being were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 67 publications
7
40
0
8
Order By: Relevance
“…Studies indicate that patients with chronic kidney disease can enhance spirituality religiously or existentially, thereby increasing the purpose of life. Spirituality has an effect on the way people cope by controlling the stress of the disease, regulating mental health, and improving quality of life (14) . In a study conducted in Iran (14) , it was found that the feeling of belonging to a sublime being and having the support of God helps religious people minimise stress when confronted with distressing life events, and better adapt physically, mentally, socially and spiritually to these events.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that patients with chronic kidney disease can enhance spirituality religiously or existentially, thereby increasing the purpose of life. Spirituality has an effect on the way people cope by controlling the stress of the disease, regulating mental health, and improving quality of life (14) . In a study conducted in Iran (14) , it was found that the feeling of belonging to a sublime being and having the support of God helps religious people minimise stress when confronted with distressing life events, and better adapt physically, mentally, socially and spiritually to these events.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes threatens the physical, social, functional, and emotional well-being of patients and must face many struggles associated with this diagnosis (Jafari et al 2014;Karimi Moonaghi et al 2014). Religion plays an important role in coping with diabetes by enhancing patients' empowerment (Abdoli et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies outline various strategies to cope with DD for T2DM outpatients, such as spirituality [19], selfmanagement [18] and family and social support [20][21][22][23][24]. Spirituality is a coping mechanism that is used in several countries, such as Iran [25], Georgia [26] and Malaysia [27]. In Indonesia however, the connection between DD and coping mechanisms is poorly understood.…”
Section: Introductionmentioning
confidence: 99%